2002
DOI: 10.1021/cm021101u
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Structure of CuOx/CeO2 Nanocomposite Catalysts Produced by Inert Gas Condensation:  An HREM, EFTEM, XPS, and High-Energy Diffraction Study

Abstract: Inert gas condensation (IGC) has been employed to produce nanoparticles of the low-temperature combustion catalyst CuO x /CeO2. For the first time we have used a multiple heating crucible setup to tailor various morphologies over the whole compositional range (2−98% Cu). The factors that control the growth, structure, and morphology of the nanocomposite have been studied. A powerful combination of complementary characterization methods has been used to elucidate the catalytic synergistics of this material. Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…The {1 1 0} and {0 0 1} planes are less stable compared to the {1 1 1} planes. Therefore {1 1 1} planes are inherently less reactive [20][21][22]. Yang et al [23] found that adsorption of CO on {1 1 1} is weak, whereas there are both weak and strong adsorptions on the {1 1 0} plane.…”
Section: Hrtem Analysis Of Nanoceriamentioning
confidence: 99%
“…The {1 1 0} and {0 0 1} planes are less stable compared to the {1 1 1} planes. Therefore {1 1 1} planes are inherently less reactive [20][21][22]. Yang et al [23] found that adsorption of CO on {1 1 1} is weak, whereas there are both weak and strong adsorptions on the {1 1 0} plane.…”
Section: Hrtem Analysis Of Nanoceriamentioning
confidence: 99%
“…[12][13][14] For instance, Huang et al have reported that a CuO modified USY zeolite possessed good activity and high selectivity for Cl-VOC decomposition. 15 Adding ceria as a promoter to copper oxide has many advantages for catalytic performance: 1) it stabilizes the dispersion of the active Cu phase; 16 2) it acts as an oxygen storing phase (Ce 3+ /Ce 4+ ) and strongly affects the copper redox properties; [17][18][19][20] and 3) it creates structural defects and improves the oxygen storage capacity and diffusivity. 19,21,22 However, studies concerning the low-temperature catalytic combustion of HCVOCs using CuO-CeO 2 have seldom been reported, despite the material being proven to have excellent catalytic activities for the oxidation of many VOC pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CuO exhibits high mechanical strength, high-temperature durability, giant magnetoresistance and piezoelectricity. Apart from being an excellent catalytic material for CO oxidation, it has been widely used in indoor air cleaning and automotive exhaust treatment [33].…”
Section: Introductionmentioning
confidence: 99%